Spermine: Its Emerging Role in Regulating Drought Stress Responses in Plants - Hasan, Md Mahadi; Skalicky, Milan; Jahan, Mohammad Shah; Hossain, Md Nazmul; Anwar, Zunaira; Nie, Zheng-Fei; Alabdallah, Nadiyah M; Brestic, Marian; Hejnak, Vaclav; Fang, Xiang-Wen (Cells, 2021)
In recent years, research on spermine (Spm) has turned up a lot of new information about this essential polyamine, especially as it is able to counteract damage from abiotic stresses. Spm has been shown to protect plants from a variety of environmental insults, but whether it can prevent the adverse effects of drought has not yet been reported. Drought stress increases endogenous Spm in plants and exogenous application of Spm improves the plants' ability to tolerate drought stress. Spm's role in enhancing antioxidant defense mechanisms, glyoxalase systems, methylglyoxal (MG) detoxification, and creating tolerance for drought-induced oxidative stress is well documented in plants. However, the influences of enzyme activity and osmoregulation on Spm biosynthesis and metabolism are variable. Spm interacts with other molecules like nitric oxide (NO) and phytohormones such as abscisic acid, salicylic acid, brassinosteroids, and ethylene, to coordinate the reactions necessary for developing drought tolerance. This review focuses on the role of Spm in plants under severe drought stress. We have proposed models to explain how Spm interacts with existing defense mechanisms in plants to improve drought tolerance.
Keywords: polyamines; abscisic acid; období sucha; Stress, Physiological; oxidační stres; antioxidant enzymes; fyziologický stres; Spermine; drought; stomata; Adaptation, Physiological; rostliny; fyziologická adaptace; Droughts; Oxidative Stress; Plants; spermin